1990
DOI: 10.1007/bf01129655
|View full text |Cite
|
Sign up to set email alerts
|

A Topographic study of differences in the P300 between introverts and extraverts

Abstract: This paper presents results of a study to establish a link between neurocognitive psychophysiological and psychological type data through the investigation of differences in topographic auditory event-related potential (AERP) (P300) patterns in strongly introverted (n = 17) and strongly extraverted ( = 16) high school males as identified by the Myers Briggs Type Indicator. Group data files were created for the auditory event related potential task and converted to ASCII form. Amplitude values were evaluated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Daruna et al ( 1985) found the expected result in a stimulus-guessing task. as did Wilson and Languis ( 1990) in a conventional oddball task. However.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Daruna et al ( 1985) found the expected result in a stimulus-guessing task. as did Wilson and Languis ( 1990) in a conventional oddball task. However.…”
Section: Introductionmentioning
confidence: 80%
“…1985;Ditraglia & Polich, 1991;O'Connor, 1983: Orlebeke, Kok & Zeillemaker, 1989: Polich & Martin, 1992Pritchard, 1989: Wilson & Languis, 1990. The studies have generally adhered to the auditory oddball paradigm, or some variation thereof.…”
Section: Introductionmentioning
confidence: 99%
“…One may therefore conclude that the reduction in the P300 amplitude indicates the amount of effort that was necessary to compensate for arousal conditions being less optimal for the respective group. The effect of larger P300 amplitudes of introverts in monotonous oddball tasks of longer duration reported in Daruna et al (1985), Ditraglia and Polich (1991), Ortiz and Maojo (1993), Polich and Martin (1992), and Wilson and Languis (1990) may also indicate that extraverts had to invest more effort than introverts under conditions of less optimal arousal.…”
Section: Introductionmentioning
confidence: 83%
“…A decreased amplitude of the Р3 is a significant marker of predisposition to alcoholism and drug addiction [129]. Noticeable correlations between the Р3 parameters and the peculiarities of the temperament and character of individuals were also found [130][131][132].…”
Section: Components Of Eps and Their Possible Functional Correlatesmentioning
confidence: 95%
“…It should, however, be emphasized that the opinions of different researchers on the pattern of such relations are in many cases contradictory. Observations of a few authors indicated that the amplitude of the Р3 in introverts is higher than that in extraverts [164], and the most clearly expressed (significant) differences were observed in the central/parietal/occipital regions [130]. As was supposed [165], the greater Р3 component in introverts is related to the greater level of voluntary attention in these subjects and also to the higher level of general cerebral activation [166].…”
Section: Correlation Of the Characteristics Of Eeg Eps With Peculiarimentioning
confidence: 97%